Comparing fiscal multipliers across models and countries in Europe - Juha Kilponen; Massimiliano Pisani; Sebastian Schmidt; Vesna Corbo; Tibor Hledik; Josef Hollmayr; Samuel Hurtado; Paulo Júlio; Dmitry Kulikov; Matthieu Lemoine; Matija Lozej; Henrik Lundvall; et al. (National Bank of Belgium, 2015)
This paper employs fifteen dynamic macroeconomic models maintained within the European System of Central Banks to assess the size of fiscal multipliers in European countries. Using a set of common simulations, we consider transitory and permanent shocks to government expenditures and different taxes. We investigate how the baseline multipliers change when monetary policy is transitorily constrained by the zero nominal interest rate bound, certain crisis-related structural features of the economy such as the share of liquidity-constrained households change, and the endogenous fiscal rule that ensures fiscal sustainability in the long run is specified in terms of labour income taxes instead of lump-sum taxes.
Keywords: E12; E13; E17; E62; E63; 330; Fiscal policy; Output multipliers; Model comparison; Zero lower bound; Finanzpolitik; Multiplikator; Vergleich; Ganzzahlige Optimierung; EU-Staaten